Translation – Theory and Technology - Bréard, Andrea; Tamborini, Marco (Peter the Great St. Petersburg Polytechnic University, 2024)
For the editorial Introduction to the special issue, see Bréard, A. & Tamborini, M. (2024) "Translation: The Interfaces of Language and Technology